PENATALAKSANAAN FISIOTERAPI PADA PEMAIN FUTSAL TERHADAP PENINGKATAN KEKUATAN OTOT TUNGKAI DENGAN LATIHAN LYING LEG CURL - Aienal Ahyar; Wanti Hasmar; Putra Hadi (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2022)
Background : Muscle strength is the maximum force, force or tension that a muscle or muscle group can produce. A person may have strength in certain muscle parts but not necessarily in other muscle parts, for example in futsal players who tend to take advantage of leg muscle strength. This muscle strength is a very important component in maximum achievement in playing futsal. Therefore it is very necessary to maintain or maximize the strength of these muscles. Objective : To find out the benefits of Lying Leg Curl weight training on leg muscle strength. Method : A case study with 1 respondent using a vertical jump test to measure leg muscle strength. Results : After doing weight training therapy for 12 times with 3 sets of exercises consisting of 1-8 repetitions and 2-5 minutes of rest with a load of 80% of 1RM the results were an increase in leg muscle strength. Conclusion : Lying leg curl weight training with the principle of 1RM can maximize/improve the leg muscle ability of futsal players.